A rare case of myxoma mimicking pulmonary thromboembolism: a case report - Hajsadeghi, Shokoufeh; Hosseini, Saeid; Saidi, Hossein; Mirshafiee, Shayan (Frontiers in Cardiovascular Medicine, 2024)
Studies have shown that primary cardiac tumors are exceptionally rare and among them myxomas represents approximately half. Although majority of these benign tumors are located in left atrium, they can also emerge in the right cardiac chambers and also on cardiac valves. In rare instances, they may extend into the great vessels. In this case, we present a teenage girl with a past medical history of successfully cured acute lymphoblastic leukemia, who presented with progressive dyspnea and lower limbs edema. Based on history, laboratory, and echocardiographic evidences, she was initially treated for high-risk thromboembolism but after inefficient response, she underwent surgery, with a large right ventricular outflow tract myxoma being diagnosed.